2017
DOI: 10.1007/s00253-017-8658-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced avermectin production by Streptomyces avermitilis ATCC 31267 using high-throughput screening aided by fluorescence-activated cell sorting

Abstract: Avermectins, produced by Streptomyces avermitilis, are important antiparasitic agents. The use of traditional microbial breeding methods for this organism has been limited by the low-throughput shake flask-based screening process. The unique growth cycle of actinomycetes makes the establishment of a reliable high-throughput screening (HTS) process difficult. To enhance the efficiency of screening strains with high yields of avermectin, a HTS process aided by fluorescence-activated cell sorting (FACS) was estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
0
22
0
1
Order By: Relevance
“…Cao et al. established a reliable high‐throughput screening (HTS) strategy integrating fluorescence‐activated cell sorting and random mutagenesis for screening high avermectin titer S. avermitilis mutants. They reported that a high‐titer avermectin producer (G9) was obtained from 5760 mutants after mutagenesis and HTS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cao et al. established a reliable high‐throughput screening (HTS) strategy integrating fluorescence‐activated cell sorting and random mutagenesis for screening high avermectin titer S. avermitilis mutants. They reported that a high‐titer avermectin producer (G9) was obtained from 5760 mutants after mutagenesis and HTS.…”
Section: Resultsmentioning
confidence: 99%
“…The ZJAV-Y-HS mutants was found to provide the best production, with maximal production of 4632.17 μg/mL of avermectin and other analogue after 240 h. Among the ZJAV-Y-147 and ZJAV-Y-HS mutants and the wild-type strain, the ZJAV-Y-147 mutant was found to provide the best production, yielding maximal production of 4822.23 μg/mL of the B1a component of avermectin as estimated by HPLC-UV. Cao et al [32] established a reliable high-throughput screening (HTS) strategy integrating fluorescence-activated cell sorting and random mutagenesis for screening high avermectin titer S. avermitilis mutants. They reported that a high-titer avermectin producer (G9) was obtained from 5760 mutants after mutagenesis and HTS.…”
Section: Production Of Avermectin B1a and Its Analogs By The Mutants mentioning
confidence: 99%
“…周扬等人 [97] 通过活跃链霉菌产生的那 西肽对藤黄微球菌具有抑制效果, 根据抑菌圈的大 小经高通量筛选获得了那西肽高产菌株. Cao等人 [98] 通过对孢子进行碘化丙锭(PI)和二乙酸荧光素(FDA) 染色, 利用流式细胞仪分选活性孢子, 高通量筛选了 阿维菌素高产菌株. Zeng等人 [99] Figure 3 (Color online) The process of microbial high throughput screening 型在菌株之间的传递成为可能 [104] .…”
Section: 体生长情况及其代谢特性 如营养缺陷型、耐受性、 水解圈、显色圈、抑菌圈等;unclassified
“…Although ARTP has several outstanding advantages over other conventional methods, including rapid mutation rate and high operational flexibility (Zhang et al, 2014). In order to obtain a desired target, a single ARTP treatment or an iterative ARTP treatment is usually performed (Wang et al, 2010; Zhang et al, 2015; Ren et al, 2017; Cao et al, 2018). Interestingly, in previous studies, ARTP treatment was also combined with other treatments such as single resistance screening (Liang et al, 2015; Ren et al, 2017), or radiation mutagenesis with UV (Zhang et al, 2015) to improve the overall efficiency.…”
Section: Introductionmentioning
confidence: 99%